Epigenome-wide analysis in familial hypercholesterolemia identified new loci associated with high-density lipoprotein cholesterol concentration. (December 2012) - Guay, Simon-Pierre; Voisin, Gregory; Brisson, Diane; Munger, Johannie; Lamarche, Benoît; Gaudet, Daniel; Bouchard, Luigi
Aim: This study aims to assess whether epigenetic changes may account for high-density lipoprotein cholesterol (HDL-C) level variability in familial hypercholesterolemia (FH), a recognized human model to study cardiovascular disease risk modulators.Materials & methods: A genome-wide DNA methylation analysis (Infinium HumanMethylation27 BeadChip, Illumina) was performed on peripheral blood DNA samples obtained from men with FH with low (n = 10) or high (n = 11) HDL-C concentrations. The initial association with one of the top differentially methylated loci located in the promoter of the TNNT1 gene was replicated in a cohort of 276 FH subjects using pyrosequencing.Results: According to the Ingenuity Pathway Analysis software, the HDL-C differentially methylated loci identified were significantly associated with pathways related to lipid metabolism and cardiovascular disease. TNNT1 DNA methylation levels were positively correlated with mean HDL particle size, HDL-phospholipid, HDL-apolipoprotein AI, HDL-C and TNNT1 expression levels.Conclusion: These results suggest that epigenome-wide changes account for interindividual variations in HDL particle metabolism and that TNNT1 is a new candidate gene for dyslipidemia.